2021
DOI: 10.36311/jhgd.v31.11071
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of motor development and quality of life in the context of child obesity

Abstract: Introduction: Child development is a period of progressive and complex transformations related to growth, maturation, learning, motor skills, and psychosocial issues. Objective: Analyze the influence of obesity on the aspects of motor development and quality of life of children aged three to eight years, and and their mothers’ levels of anxiety and depression. Methods: Cross-sectional descriptive and quantitative approach study with children enrolled and attended at a pediatric endocrinology in Fortaleza, CE, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
2
4
0
Order By: Relevance
“…The mechanisms described for this relationship reinforce the role of parental practices that affect children's behaviors related to physical activity, eating and screen use 36,37 . In Brazil, recent studies have also reported similar results 38,39 . In a study developed with children treated at a pediatric endocrinology out patient clinic located in the city of Fortaleza, Ceará, researchers showed a bidirectional relationship between mothers' depression and children's obesity 38 .…”
Section: Discussionsupporting
confidence: 58%
“…The mechanisms described for this relationship reinforce the role of parental practices that affect children's behaviors related to physical activity, eating and screen use 36,37 . In Brazil, recent studies have also reported similar results 38,39 . In a study developed with children treated at a pediatric endocrinology out patient clinic located in the city of Fortaleza, Ceará, researchers showed a bidirectional relationship between mothers' depression and children's obesity 38 .…”
Section: Discussionsupporting
confidence: 58%
“…This observation took place among a healthy sample that represented the majority of the population in these age groups, with the subjects falling within the healthy weight to overweight range. In another recent study conducted by Martins et al (2021), there was a correlation between obesity and several negative outcomes, including impaired motor skill development and a worsened quality of life. This was evidenced by the obese individuals' lower scores in the areas of emotional well-being and physical.…”
Section: Favieri Et Al (2021)mentioning
confidence: 96%
“…In this way, the JHGD, as it does throughout its 31 years of uninterrupted publication, contributes to this debate, and in this issue 30.1 brings good and fruitful discussions about Public Health and the pandemic of COVID-19 [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] , with emphasis on the use of fear scale for COVD-19 13 .…”
Section: Coronavirusmentioning
confidence: 98%